Interaction in the course of Pre-trial Investigation of Criminal Offences Committed in the Sphere of Economic Activity Using Forged Documents (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The study is devoted to a comprehensive analysis of the peculiarities of interaction in the course of pre-trial investigation of criminal offences committed in the sphere of economic activity using forged documents. The relevance of the topic is due to the increase in the number of such crimes, their transnational nature, the use of the latest technologies, and the need to ensure effective coordination between investigative, operational, expert, and supervisory bodies. The aim of the study is to identify the theoretical, legal and organisational aspects of interaction between participants in criminal proceedings and to develop practical recommendations for its improvement.The methodological basis consists of general scientific and special methods – systemic-structural, comparative-legal, formal-dogmatic, modelling, analysis and synthesis. The scientific basis of the study is formed on the basis of the works of Ukrainian and foreign scientists in the field of criminology, criminal procedure and the organisation of law enforcement agencies.The article substantiates the theoretical foundations of interaction between subjects of pre-trial investigation, reveals the essence of communication and coordination mechanisms, and characterises the forms of cooperation between investigative bodies and operational units, expert institutions, regulatory authorities and international law enforcement structures. Particular attention is paid to the role of expert research in proving document forgery, problems of procedural use of materials from operational and investigative activities, and issues of regulatory support for interaction.Current trends in the development of interaction are identified, including the digitisation of investigative activities, the introduction of information systems for data exchange, the strengthening of cybersecurity requirements, and the adaptation of investigation methods to the conditions of martial law. It is concluded that improving the effectiveness of cooperation is possible provided that the regulatory framework is improved, the organisational structure is optimised, international cooperation is developed, and the qualifications of participants in criminal proceedings are improved.